Evaluation of Bonding Adhesion Strength and Failure Modes of Different Types of Cutback Asphalts - Falih, Teeba; Abed, Alaa H. (Al-Nahrain Journal for Engineering Sciences, 2024)
A tack coat is a minimal coating of asphalt cement, cut-back asphalt, or asphalt emulsion to an existing pavement surface between layers to guarantee proper bonding between the two layers and longitudinal and transverse joints. Numerous researchers have assessed interlayer adhesion employing failure-mode behavior tests, such as pull-off, direct shear, and torsion testing. This study aims to quantify the best tensile resistance obtained using three types of cutback asphalt (RC70, RC800 modified with polymer 4.5% & MC70). All are applied on concrete surfaces at a rate of 0.5 L/m². The Proceq DYNA Z16 pull–off tester is used to measure the tensile strength at a rate of 0.25 kN/s. It is found that the average tensile strength of the tack coat materials is (0.319, 0.138, 0.028) MPa, respectively. It is concluded that RC70 has the maximum tensile strength. Also, the different types of solvent affect adhesion strengths; RC70 was Prepared using gasoline, while MC70 used petroleum. Gasoline has greater volatility and thus increased adhesion. Failure strength modes of interior bonding varied between cohesive failure adhesive and adhesive failure.